2012
DOI: 10.4315/0362-028x.jfp-11-288
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ozone and Chlorine in Low Concentrations as Sanitizing Agents of Chicken Carcasses in the Water Immersion Chiller

Abstract: The aim of this study was to investigate the effects of the use of chlorine or ozone as sanitizing agents in the water of chicken immersion chilling, using the residual levels usually applied in Brazil (1.5 ppm), comparing the effects of these treatments on the microbiological, physicochemical, and sensory characteristics of carcasses. Chicken carcasses were chilled in water (4°C) with similar residual levels of ozone and chlorine until reaching temperatures below 7°C (around 45 min). The stability of carcasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…During cooling, the slaughterhouse applied sodium hypochlorite combined with low temperature, which contributed to the reduction of Campylobacter. Chlorine has been known to have bactericidal effect, and has been applied on microbial contamination during chicken processing (25). A previous study from South California also showed a significant decrease of the Campylobacter contamination load for 0.97 logCFU/g after the water cooling process (7,26).…”
Section: Discussionmentioning
confidence: 95%
“…During cooling, the slaughterhouse applied sodium hypochlorite combined with low temperature, which contributed to the reduction of Campylobacter. Chlorine has been known to have bactericidal effect, and has been applied on microbial contamination during chicken processing (25). A previous study from South California also showed a significant decrease of the Campylobacter contamination load for 0.97 logCFU/g after the water cooling process (7,26).…”
Section: Discussionmentioning
confidence: 95%
“…The average reductions of 1.5-log 10 /ml on the skin surface and 1.0-log 10 /ml in SC that have been reported in the soaking approach are inconsistent with an earlier study by Sheldon and Brown in 1986 that reported 0.6-log 10 reduction in Salmonella after exposing to ozonated water with a concentration ranging from 3.0 to 4.5 ppm for 25 min exposure (Yang and Chen, 1979). In 2012, Trindade and colleagues reported 2.0-3.0-log 10 reduction in the Salmonella-contaminated chicken carcass after 30 min exposure to 6.0 ppm ozonated water (Trindade et al, 2012). In 1979, Yang and Chen reported a reduction rate of 7.08-log 10 in Salmonella load for ozonated water of 19.0 ppm with a maximum reduction occurring between 2 and 3 min of exposure (United States Department of Agriculture, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…Its strong oxidizing nature makes ozone a useful tool for the inactivation of bacteria, fungi, and viruses (Mercogliano, Felice, Murru, & Santonicola, ). Ozone causes damages to the bacterial membrane by breaking down the structure of glycoproteins, glycol lipids, and certain amino acids (such as tryptophan), and on the sulphydryl groups resulting in the disruption of the normal cell (Trindade, Kushida, Montes Villanueva, Pereira, & Oliveira, ).…”
Section: Physical Processing Interventionsmentioning
confidence: 99%
“…Santonicola, 2014). Ozone causes damages to the bacterial membrane by breaking down the structure of glycoproteins, glycol lipids, and certain amino acids (such as tryptophan), and on the sulphydryl groups resulting in the disruption of the normal cell(Trindade, Kushida, Montes Villanueva, Pereira, & Oliveira, 2012).Because of the short-lived nature of ozone, it must be generated on-site, leading to higher operating costs than other modes of disinfection(Jansen, Reich, & Klein, 2014). Ozonization has been used as a disinfectant treatment in the poultry industry in several studies with varying success.…”
mentioning
confidence: 99%